2013
DOI: 10.1101/cshperspect.a012005
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nucleus Accumbens CREB and Dynorphin in Dysregulation of Motivation

Abstract: Psychostimulants such as amphetamine and cocaine are believed to produce dependence by causing rapid, supraphysiological elevations in synaptic dopamine (DA) within the nucleus accumbens (NAc) (Volkow et al. 2009, Neuropharmacology 56: 3 -8). These changes in forebrain DA transmission are similar to those evoked by natural reinforcers (Louilot et al. 1991, Brain Res 553: 313 -317;Roitman et al. 2004, J Neurosci 24: 1265-1271), but are of greater magnitude and longer duration. Repeated drug exposure causes com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 137 publications
3
59
1
1
Order By: Relevance
“…In line with our findings, others have shown that CREB over-expression in accumbens reduces sucrose preference (Barrot et al 2002), induces depressive-like behavior (Pliakas et al, 2001), and is associated with aversive states of drug withdrawal (Muschamp and Carlezon, 2013). Our earlier study on mPFC D1R overexpression demonstrated a reduction in D2 receptors in the NA (Sonntag et al, 2014).…”
Section: 0 Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our findings, others have shown that CREB over-expression in accumbens reduces sucrose preference (Barrot et al 2002), induces depressive-like behavior (Pliakas et al, 2001), and is associated with aversive states of drug withdrawal (Muschamp and Carlezon, 2013). Our earlier study on mPFC D1R overexpression demonstrated a reduction in D2 receptors in the NA (Sonntag et al, 2014).…”
Section: 0 Discussionsupporting
confidence: 92%
“…Increases in the transcription-regulating factor CREB (cAMP response element-binding protein) in the NA play a role in depressive- and anxiety-like states (Carlezon et al 2005) in general and following drug-withdrawal (Muschamp and Carlezon 2013). For example, increased accumbens CREB levels are associated with increased immobility in the forced swim test (Pliakas et al 2001) and following cocaine withdrawal (Chandra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…27 It is well known that dynorphin-enkephalin neuropeptide processing is regulated by CREB in response to alcohol and other drugs of abuse, in particular, drug-induced aversive effects. 36 It is likely that deficits in dynorphin-enkephalin neuropeptide processing in the NAc of ENT1 −/− mice may play a role in dampening any ethanol-induced aversive effects, thus partly explaining the ability for this mouse model to excessively consume ethanol. More importantly, these findings provide further evidence supporting a relationship between deficits in ENT1 and adenosinergic signaling via the A 2A receptor, resulting in decreased enkephalin production in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Dynorphin mediated activation of CREB is postulated to be the cause of relapse, where drug taking activities are resumed in order to decrease the adverse effects of withdrawal. For a recent review on the role of CREB and dynorphin see (Muschamp & Carlezon, 2013). The role Sal A in modulating CREB levels remains to be determined.…”
Section: Signalling Pathways Regulated By Salvinorin Amentioning
confidence: 99%